Stable Radical Cations of N, N′‐Diarylated Dihydrodiazapentacenes. Issue 1 (16th December 2019) - Xie, Gaozhan; Brosius, Victor; Han, Jie; Rominger, Frank; Dreuw, Andreas; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: A series of quinoidal N, N′ ‐diaryldiaza‐ N, N′ ‐dihydropentacenes (Quino) was prepared in a two‐step reaction, starting from quinacridone. Oxidation of Quino furnishes stable radical cations, isoelectronic to the radical anions of the azaacenes, whereas the dicationic species are isoelectronic to neutral azapentacenes. The spectroscopic properties of the diaryldiazapentacenes and their oxidized mono‐ and dications are equivalent to that of the dianion of tetraazapentacene (TAP), its radical anion and the neutral TAP. Abstract : Radicalized : A series of quinoidal N, N ′‐5, 7, 12, 14‐tetraaryl‐5, 12‐dihydropentacenes were oxidized into their radical cations and dications, the latter electronically resembling highly acceptor‐substituted diazapentacenes.